The Oxford Handbook of Food, Politics, and Society 2014
DOI: 10.1093/oxfordhb/9780195397772.013.023
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy of Regulation of Biotechnology in Agriculture

Abstract: In Europe and in many developing countries, genetically modified (GM) crops are effectively banned. Some countries limit the direct use of such crops as food for human consumption to a few niche agricultural products, such as papaya, sweet corn, and squash. These restrictions can be traced to public decision-making processes reflecting the interplay of sometimes conflicting economic interests of different groups within society. This chapter examines the political economy underlying the regulation of biotechnol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 3 publications
0
66
0
Order By: Relevance
“…Their objective function may not only be based on the direct benefits and costs of the GRS. A number of political economy models have been developed to analyze policies related to the introduction of GE crops in more detail considering two or more lobby groups (e.g., Graff et al, 2009;Swinnen and Vandemoortele, 2010) and the role of media (Vigani and Olper, 2014 anti-genetically modified organism (GMO) strategy has been a successful fundraising strategy for environmental lobby groups such as Greenpeace or Friends of the Earth. The role of anti-GMO lobby groups and their strong influence on decision making, particularly in developing countries, has been well described by political scientists (e.g., Paarlberg, 2008;Herring, 2010).…”
Section: The Real Option Model Of Perceived Costsmentioning
confidence: 99%
“…Their objective function may not only be based on the direct benefits and costs of the GRS. A number of political economy models have been developed to analyze policies related to the introduction of GE crops in more detail considering two or more lobby groups (e.g., Graff et al, 2009;Swinnen and Vandemoortele, 2010) and the role of media (Vigani and Olper, 2014 anti-genetically modified organism (GMO) strategy has been a successful fundraising strategy for environmental lobby groups such as Greenpeace or Friends of the Earth. The role of anti-GMO lobby groups and their strong influence on decision making, particularly in developing countries, has been well described by political scientists (e.g., Paarlberg, 2008;Herring, 2010).…”
Section: The Real Option Model Of Perceived Costsmentioning
confidence: 99%
“…For example, in the case of genetically modified food, the farm lobby in Europe has joined forces with several constituencies in order to prevent domestic production and importation of products that may contain genetically modified organisms (Graff, Hochman, and Zilberman 2009;Evenson and Raney 2007). These constituencies include environmentalists concerned with the impact on the local environment of growing genetically modified crops, consumers worried about the safety of food containing genetically modified organisms, and life-science companies with patents threatened by the emergence of generic crop-protection products.…”
Section: Prospects For Further Policy Reformmentioning
confidence: 99%
“…Generally speaking, there are two major viewpoints about agricultural support. One opinion issues that politicians who support farmers are to obtain more political votes (Swinnen 1994;Graff et al 2009;Anderson and Swinnen 2010;Anderson et al 2013), while other people declare that the reasons for governments to subsidize agriculture are that agriculture has an intrinsic weakness because the demand for agricultural products are inelastic but the supply of them are elastic (Zhang 1949;Krueger et al 1988;Zietz and Valdts 1993). Most of the studies which are based on developed countries followed the political support assumption, while other studies which focused on developing countries sustained a weak agriculture assumption.…”
mentioning
confidence: 99%
“…Their studies found that high-income countries are more pro-agricultural than the low-income countries and a high RRA results in high welfare losses. Graff et al (2009) declared that the politicians support agriculture because they can acquire more votes by agricultural subsidy. Another Europe-based study drew by Greenaway and Swinnen (2009) also emphasized the distorting effects of agricultural subsidy.…”
mentioning
confidence: 99%